Перенос излучения в плоском слое рассеивающей среды при наклонном освещении - Савельев Б. А.; Горячев Б. В. Борис Валентинович; Могильницкий С. Б. Сергей Борисович; Кутлин А. П.; Ларионов В. В. Виталий Васильевич (Томск, 1984)
Деп. в ВИНИТИ 19.06.84, № 4088-84